The dynamics of intraguild predation in Chrysomya albiceps Wied. (Diptera : Calliphoridae): Interactions between instars and species under different abundances of food - Rosa, Gisele S.; de Carvalho, Lidia R.; dos Reis, Sergio F.; Godoy, Wesley A. C. (Entomological Society Brasil, 2006)
The pattern of larval interaction in blowflies confined with Chrysomya albiceps Wied. and C. rufifacies Maquart can be changed in response to the predatory behaviour of the two species to a contest-type process instead of the scramble competition that usually occurs in blowflies. Facultative predation is a frequent behaviour in C. albiceps and C. rufifacies that occurs as an alternative food source during the larval stage. In this study, we investigated the dynamics of intraguild predation by C. albiceps on other fly species in order to analyse interspecific and intraspecific survival in C. albiceps, C. megacephala and C macellaria Fabricius. The experimental design of the study allowed us to evaluate how factors such as species, density and abundance of food influenced the survival of the calliphorid species. When C albiceps was confined with C megacephala or C macellaria, only adults of C albiceps survived at different larval densities and abundance of food. In addition, the survival of C albiceps was higher in two-species experiments when compared to single species experiments. The implications of these results for the dynamics of C albiceps were discussed.
Keywords: larval behavior; blowfly; competition